2019
DOI: 10.1016/j.redox.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel platinum complex containing a piplartine derivative exhibits enhanced cytotoxicity, causes oxidative stress and triggers apoptotic cell death by ERK/p38 pathway in human acute promyelocytic leukemia HL-60 cells

Abstract: Piplartine (piperlongumine) is a plant-derived compound found in some Piper species that became a novel potential antineoplastic agent. In the present study, we synthesized a novel platinum complex containing a piplartine derivative cis-[PtCl(PIP-OH)(PPh3)2]PF6 (where, PIP-OH = piplartine demethylated derivative; and PPh3 = triphenylphosphine) with enhanced cytotoxicity in different cancer cells, and investigated its apoptotic action in human promyelocytic leukemia HL-60 cells. The structure of PIP-OH ligand w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…As noted above, chemotherapy and radiotherapy cause an increase in intracellular ROS that can lead to apoptosis 92,93 via extrinsic or intrinsic pathways 94,95 . Many drugs used in anticancer therapy induce oxidative stress.…”
Section: Ros and Apoptosis (Type I Programmed Cell Death)mentioning
confidence: 97%
“…As noted above, chemotherapy and radiotherapy cause an increase in intracellular ROS that can lead to apoptosis 92,93 via extrinsic or intrinsic pathways 94,95 . Many drugs used in anticancer therapy induce oxidative stress.…”
Section: Ros and Apoptosis (Type I Programmed Cell Death)mentioning
confidence: 97%
“…In addition, we discovered that these alterations are related with AKT, ERK/ P38 and Slug pathways. Researches show that AKT, ERK/ P38 and Slug pathways are all involved in the regulation of various biological processes and promote tumorigenesis (Cho et al 2019;Oliveira et al 2019;Revathidevi et al 2019). Moreover, the AKT, ERK/P38 and Slug pathways are activated by diverse cellular stimuli regulating various physiological functions such as cell growth, cell survival, cell cycle progression, protein translation and metabolism (Cho et al 2019;Oliveira et al 2019;Revathidevi et al 2019).…”
mentioning
confidence: 99%
“…Researches show that AKT, ERK/ P38 and Slug pathways are all involved in the regulation of various biological processes and promote tumorigenesis (Cho et al 2019;Oliveira et al 2019;Revathidevi et al 2019). Moreover, the AKT, ERK/P38 and Slug pathways are activated by diverse cellular stimuli regulating various physiological functions such as cell growth, cell survival, cell cycle progression, protein translation and metabolism (Cho et al 2019;Oliveira et al 2019;Revathidevi et al 2019). Our results showed that down-regulation of RFWD3 significantly decreases the P-P38, P-ERK, P-AKT, Slug and N-Cadherin protein expression levels in AGS and HGC-27 cells, while the expression level of E-Cadherin is increased, suggesting that the downregulated expression of RFWD3 in gastric cell lines activated AKT, ERK/P38 and Slug signaling pathway.…”
mentioning
confidence: 99%
“…reported that p38 and extracellular signal-regulated kinase (ERK) mitogen-activated protein kinases also cause oxidative stress and apoptotic cell death in HL-60 cells treated with natural products. [19,20] However, activation of p38 and ERK was not observed in citbismine-E-treated HL-60 cells by immunoblotting of active phosphorylated form (data not shown). To investigate the involvement of JNK signalling pathway further in cibistamine-E-induced cell death, we examined the effect of a selective inhibitor of JNK, JNK-IN-8, on cibistamine-E-induced caspase activation and subsequent apoptosis.…”
Section: Resultsmentioning
confidence: 87%